Seeing art from the studio: the inseparability of artistic process, place of creation, and meaning (Revista Apotheke, 2026)
This article seeks to deepen research into artistic processes from a perspective that focuses on the creative space—studios—in its multiple meanings, in order to reach layers of meaning that can be recognized in the finished works in an exhibition environment. To this end, a case study was conducted on the process of Rodrigo Dulcio, an artist of the 2000 generation, sculptor, and designer residing in Curitiba, Paraná, Brazil. The methodological approach for this study was provided by the movements of approximation and distancing from the studio space and the creative process. This approach allowed for immersion in the creative process and a panoramic view of it in relation to the local artistic field. To this end, a theoretical framework was adopted that sought to understand the experience of the creative space based on John Dewey and the creative process as the habitus of a field, based on Pierre Bourdieu. In this way, it was possible to verify how much the place of creation is intertwined with the creative process and how much this intertwining clarifies the relationships between the poetics of artists of the same generation and those of local predecessors and art history.
Keywords: creative process; studio; meaning; drawing; sculpture